PREVALENCE OF BODY PIERCING AND TATTOOING AND KNOWLEDGE OF ASSOCIATED HEALTH RISKS AMONG UNDERGRADUATES IN UNIVERSITY OF IBADAN, NIGERIA (2015)
Body Piercing and Tattooing (BPT) can increase the risk of contracting infectious diseases. Despite the potential harmful health consequences, the practice has remained attractive to young people. Body piercing (BP) includes piercing of various parts of the body excluding single piercing of both earlobes for females. Documented information on BPT and the awareness of its associated health risks among young people in Nigeria is few despite the practice. It is necessary to determine the prevalence, motivations for practicing BPT and awareness of the associated health risks among young people. This study was conducted to determine the prevalence of BPT and assess knowledge of associated health risks among undergraduates in University of Ibadan, Nigeria. A cross-sectional survey involving a 3-stage sampling technique using simple random and systematic methods were used to select 424 students in 34 rooms each from two male and two female halls of residence out of five and four halls respectively. A self-administered semi-structured questionnaire was used to collect information on socio-demographic characteristics, knowledge of health risks associated with BPT and practice of BPT. Knowledge of health risks associated with BPT was assessed on a 39-point scale and scores ≥20 was considered good. Data were analysed using descriptive statistics and Chi-square test at 5% level of significance. Respondents’ age was 21.4±2.3 years and 50.0% were females. Prevalence of BP was 13.2% and tattooing, 1.9%. Majority (96.8%) of pierced respondents were females. Of the pierced respondents, 74.3%, 11.4%, 8.6%, 5.7% reported ear piercing, nose piercing, navel and tongue piercings respectively. Among respondents who practised BP, 87.1% were aged 20- 25 years while 12.9% were aged 16-19 years. More than half (58.1%) of the respondents who practised BP were in higher levels (300-500) and 41.9% in lower levels (100-200) of study. Reported reasons for piercing were fun (45.8%), fashion (33.3%), personal (12.5%) and desire to put on more earrings (8.3%). Half (50.0%) of tattooed respondents were females, of which 50.0% had tattooed their legs, (25.0%) chests and (25.0%) arms. Twenty six percent of respondents had good knowledge of health risks associated with BPT and 60.0% were not aware of hygienic rules regarding BPT such as use of sterilised equipment (26.5%), single use of needle (18.9%), and use of gloves (16.1%). Many respondents were aware of some health complications associated with BPT such as HIV (90.1%), keloid (84.7%), infection of site of piercing and tattoo (73.4%) and haematoma (67.6%). There was a significant difference between sex and knowledge of health risk associated with BPT. Prevalence of body piercing and tattooing was low while knowledge of associated health risks was poor among undergraduate students of University of Ibadan. Information on body piercing and tattooing and its associated health risks should be included in life building skills education programmes for the undergraduates.